Adams and Stashak's lameness in horses - Baxter, Gary M. (Hoboken, NJ : Wiley-Blackwell, 2020)
"This new edition of the go-to resource for equine lameness features updates throughout and more in-depth information on objective lameness assessment, sports medicine, rehabilitation, treatment options, and advanced imaging. With contributions from the world's leading authorities on the subject, the book covers functional anatomy, examination, imaging, lameness of the distal limb, proximal limb, and axial skeleton, principles of musculoskeletal disease, therapies, occupation-related conditions, lameness in young horses, and farriery. More than 1,700 images support the text, making it an exhaustive reference for all aspects of lameness in horses. Now in its seventh edition, Adams and Stashak's Lameness in Horses continues to be the definitive resource on equine lameness for veterinary specialists, practitioners, interns, residents, and students alike. The book is supplemented with a companion website offering a plethora of "how-to" videos demonstrating lameness examination and select perineural and intrasynovial anesthesia techniques. Adams and Stashak's Lameness in Horses is a must-have reference for any practicing large animal and equine veterinarian, equine veterinary specialist, or veterinary student dealing with lameness in the horse"--
Functional anatomy of the musculoskeletal system -- Examination for lameness -- Diagnostic imaging -- Lameness of the distal limb -- Lameness of the proximal limb -- Lameness associated with the axial skeleton -- Principles of musculoskeletal disease -- Principles of therapy for lameness -- Occupation-related lameness conditions -- Lameness in the young horse -- Foot care and farriery -- Miscellaneous musculoskeletal conditions.
Includes bibliographical references and index.
Keywords: Horse -- Fractures; Lameness in horses; Cojera en caballos; Horses -- Injuries; Caballos -- Lesiones